PENGEMBANGAN E-MODUL BERBASIS DISCOVERY LEARNING PADA MATA PELAJARAN KONTROL REFRIGERASI DAN TATA UDARA KELAS XI TEKNIK PENDINGIN DAN TATA UDARA SMK NEGERI 1 PERCUT SEI TUAN - Saskia Rehani Br Tarigan; Nelson Sinaga (Universitas Negeri Medan, 2023)
Abstract This study aims to: (1) Find out how to develop an E-Module Based on the Discovery Learning Model for Refrigeration and Air Conditioning Control for students of SMK Negeri 1 Percut Sei Tuan. (2) Knowing the feasibility level of Discovery Learning Based E-Module which was developed for students of SMK Negeri 1 Percut Sei Tuan. (3) Knowing student responses to E-Modules Based on Discovery Learning Models in Class XI of Refrigeration and Air Conditioning Control subjects at SMK Negeri 1 Percut Sei Tuan. This research will be tested by involving class XI students of Refrigeration and Air Conditioning Engineering at SMK Negeri 1 Percut Sei Tuan in the odd semester of the 2022/2023 academic year. This type of research is Research and Development (R & D) with the ADDIE research model. The ADDIE research model includes 5 stages, namely first analysis which includes product needs analysis, second design, namely compiling outlines, layouts and E-Module material, third development, namely developing products that have been designed to be validated so that they get input from media experts and material experts, the fourth is implementation, namely implementing the product to get a response from users (students) to the E-Module that has been developed, the fifth evaluation, namely evaluating the E-Module based on some input from experts and user responses. The instruments used in this study were validation questionnaires and user response questionnaires. The results of this study are known: (1) This development research produces a product in the form of an E-Module Based on the Discovery Learning Model for Refrigeration and Air Conditioning Control. (2) The feasibility of this E-Module is obtained from the validation results of media experts in the